The Strategy to Improve MSME Performance through Entrepreneurial Orientation, Organizational Readiness, Knowledge Management, and E-Commerce Adoption - 'Aliyah, Himmatul; Wahyuni , Sari (Borong Newinera Publisher, 2024)
Micro, Small and Medium Enterprises (MSMEs) are among the most important contributors to the Indonesian economy. In the digital era, using e-commerce is one of the strategies to face the increasing competition in the business world. However, MSMEs in Indonesia are still faced with various obstacles, primarily related to the lack of mastery of technology and the unoptimized utilization of e-commerce in business. Based on this, it is necessary to check the factors that can enhance MSME performance. This study aims to analyze the influence of entrepreneurial orientation, organizational readiness, knowledge management, and e-commerce adoption, which are expected to improve MSME performance in the digital era. Partial Least Squares Structural Equation Modeling (PLS-SEM) is used to test the relationship between these variables. This study involved 241 MSME owners/managers who have adopted e-commerce in their businesses in the food and beverage industry. The results showed that entrepreneurial orientation, organizational readiness, knowledge management, and e-commerce adoption can significantly improve the performance of MSMEs in food and beverage businesses. These findings better explain how MSME players can optimally improve capabilities and organizational resources to achieve sustainable competitive advantage and superior business performance.